Culturally Responsive English Teaching: Integrating Local Wisdom and Multiple Intelligences in EL Classrooms - Najib, Muhammad Reza Ainun; Aditama, Madya; Santoso, Yan Imam (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
In today’s multilingual and culturally rich classrooms, English teaching must do more than deliver grammar and vocabulary, it must reflect who the learners are. This study explores how 25 English teachers from high schools and vocational schools in Batang Regency, Indonesia, bring life to their lessons by weaving together culturally responsive pedagogy, Multiple Intelligences (MI), and local wisdom. Using a qualitative phenomenological approach, the research draws insights from interviews, classroom observations, and teaching materials to understand how teachers navigate diverse learning needs while honouring students’ cultural roots. The findings show that when local folklore, traditional arts, and community knowledge are combined with MI-based strategies like storytelling, music, movement, and peer collaboration students engage more deeply, express themselves more confidently, and feel a sense of pride in their identity. Even amid rigid curricula and limited resources, these teachers innovate from the ground up, turning their classrooms into inclusive spaces where learning becomes personal and meaningful. This study offers a fresh lens on what equitable English teaching can look like in postcolonial, multicultural contexts and reminds us that language learning is at its best when it connects not just to exams, but to who students truly are.